ADMINISTRASI PELAYANAN PENERBITAN SURAT IZIN PENANGKAPAN IKAN PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI UTARA - DJUNNA, HARISMAN; POSUMAH, JOHNNY; PALAR, NOVIE (Sam Ratulangi University, 2019)
This study is about the administration of the service of issuing permits for fishing in themarine and fisheries service of North Sulawesi Province. Public service regulations that are stillscattered in the number of regulation that are sectoral, making public services in Indonesia are ina conditional that is not yet manageable. In other words the community has not received theexcellent service that was their hope. In order to know the quality of service that is felt significantlyby consumers, there are indicators of consumer satisfaction measures that lie in the fivedimensions of service quality. 1). Tangibles : Service quality in the from of physical facilities,offices, computerized administration, waiting room, information places. 2). Reliability : The abilityand reliability to provide trusted service. 3). Responsivess : The ability to help and provideservices quickly and accurately, as well as being responsive to consumer desires. 4). Assurance :The ability and friendliness as well as the courtesy of employees in convincing consumer trust. 5).Emphaty : Firm but attentive attitude of employees toward consumers. In this study the authorsused a qualitative approach with descriptive analysis techniques, in this study primary data wereobtained from interview and could also be from the result of questionnaires, while secondary datawere obtained from documents from either the relevant agencies or other relevant agencies. Theresult have not been able to optimally meet the needs of the service user community. Researchersprovide advice on this is about these five aspects : 1). Tangibles aspects : updating both the qualityand quantity of facilities or infrastructure available at the maritime and fisheries service office inNorth Sulawesi Province. 2). Reliability aspects : Strive for the ability and reliability of officers tothe provide services by attending training, both internal and external. 3). Responsiveness aspects :Every service officer or apparatus at the North Sulawesi Province’s Office of maritime affairs andfisheries must try to increase understanding quickly and precisely on what is the problem ofservice needs desired by the community. 4). Assurance aspects : each service officer must improveattitudes towards all citizens who need service. 5). Emphaty aspects : every officer is required tohave firmness in carrying out their duties and responsibilities.Keywords : Administration, Service, Fishing License.